Preparation and Characterisation of Hydroxypropylated Crosslinked Sago Starch for Application in Acidic, Frozen and Canned Foods - Suwanliwong, Saowakon (1998)

(untitled)
Hydroxypropylation and crosslinking were carried out to improve the quality of sago starch. The optimum conditions for preparation of hydroxypropylated crosslinked sago starch were found to be an initial reaction with 10-12% propylene oxide at 40°C for 24 hr using 40% (dsb) starch slurry containing 15% sodium sulphate at pH 10.5. This was followed by crosslinking using a mixture of 2% sodium trimetaphosphate (STMP) and 5% sodium tripolyphosphate (STPP). Through hydroxypropylation, it was found that there was a significant increase in molar substitution which will in turn induce the increase in crosslinking and this was seen from the marked increase in phosphorus content and degree of substitution. This was accompanied by a significant decrease in paste clarity, swelling power and solubility compared to that of the native starch. The hydroxypropylated crosslinked sago starch prepared also exhibited desirable properties in that it exhibited no viscosity breakdown, high acid resistance, high freeze-thaw stability and improved gel texture. The hydroxypropylated crosslinked sago starch (HPST) was prepared in a larger scale having molar substitution (MS) and degree substitution (DS) values in the range of 0.038 to 0.045 and 0.004 to 0.005, respectively. The properties of HPST in tenns of sediment volume, swelling power, solubility and paste clarity were IS.7S%m1, 16.7, 8.62% and S.18 %T6so, respectively. The MS value, phosphorus content, paste clarity, swelling power and syneresis after six :freeze-thaw cycles of HPST when compared to that of commercially available modified starches which are normally used or incorporated in acidic, :frozen and canned foods did not differ significantly. The pasting characteristic of HPST exhibited thin to thick viscosity which is. similar (P>0.05) to that of commercial hYdroxypropylated crosslinked tapioca starch (NAT 8). The acid stability, solubility and :freeze-thaw stability of both starches were also similar (P>0.05) but the swelling power of HPST was slightly lower (P<0.05) than that of NAT 8.The canning stability of HPST in tenns of textural and rheological aspects was very high either in neutral or acidic canning condition at IS psig (121°C) for 30 min. However, when sterilised longer than 40 min at 121°C, the HPST pastes (6% starch solid) experienced a significant decrease in viscosity and firmness. The HPST paste which consisted of 6% starch solid and 10% sucrose at pH 6.S exhibited rapid heat penetration. A sterilisation value (Fo) of 25.48 could be obtained from the sterilisation of HPST paste contained in a can size 300x305 at 121°C for 30 min.